Exploring effects of intermittent light upon visible light promoted water oxidations. Issue 10 (2nd October 2017) - Walsh, Dominic; Patureau, Pascaline; Robertson, Karen; Reeksting, Shaun; Lubben, Anneke; Eslava, Salvador; Weller, Mark T.
Abstract : Illumination of visible light photocatalytic water oxidations using continuous or intermittent light was investigated using a range of earth abundant metal oxides. Brief light cessations allowed reduced light harvester degradation and gave an approximate doubling of yield and reaction rate. Abstract : Visible light promoted photocatalytic water oxidations for potential solar fuel production have been studied widely, with many reports on optimization of reagent components. Here we report an exploration on the effects upon ongoing reactions of daylight equivalent light intensity illumination with regulated short dark periods of a few seconds duration as compared to standard continuous illumination. Comparison was made with systems employing synthesized low cost earth abundant iron oxide, calciumoxomanganite and cobalt oxide nanoparticulate catalysts together with a [Ru(bpy)3 ] 2+ light harvesting dye and an electron acceptor. Yields of gaseous O2 and proton production were measured in situ and in real time. The study found that low cost catalysts could give very significantly increased O2 yields, turn over frequency and improved reaction profiles by use of simple on/off illumination. A range of timings with identical overall photon flux were tested and an optimum determined. Analysis of effects upon the light sensitizer under the range of lighting conditions (through mass spectrometry and UV-vis measurements), together with implementation of a continuous flow system as comparison to the batch reactions, were all employed to help elucidate the mechanisms for the clear improvements in reaction yields observed. These are believed to stem from reduction in self-decomposition of excess oxidized sensitizer and better synchronization of cyclic sensitizer oxidation/reductions with water oxidation at the metal oxide surface at specific light on : off timing.